The South Africa-Zimbabwe remittance corridor: an analysis of key drivers and constraints - Von Burgsdorff, David Kühn (School of Economics, 2020)
A considerable amount of research has been conducted on the topic of migration and remittances over the last few years, but the literature on the South Africa-Zimbabwe remittance corridor remains scarce. Using a survey conducted in April 2010 of 347 Zimbabwean migrants living in the Western Cape Province, this paper is focused on three primary aims. The first is to gain an insight into the remittance-sending behaviour and patterns of Zimbabwean migrants in South Africa. The second is to apply the survey data to assess underlying dynamics of the drivers that influence migrants’ remittance-sending decisions. The third is to analyze and discuss the constraints to remitting that Zimbabwean migrants in South Africa are faced with and that shape the remittance-sending landscape. The survey results show that remittance flows in the South Africa-Zimbabwe remittance corridor are considerable, with more than 90 per cent of Zimbabwean migrants in the sample remitting on average almost a third of their income. The most significant driver of remittances was found to be the number of dependants that migrants have in Zimbabwe. Moreover, the great majority of remittances are sent through informal channels, despite the inefficiency and high costs of these. The paper concludes that there are significant market inefficiencies and impediments in South Africa that negatively impact the flow of remittances to Zimbabwe, both by driving up costs and by excluding the majority of migrants from formal remittance channels.